Monitoring of Sedimentation on Geosynthetic Bags Installation Area in Banyuurip Mangrove Center, Ujung Pangkah, Gresik, Indonesia - Aida Sartimbul; Safitri Widya Ningtias; Citra Satrya Utama Dewi; Muhammad Arif Arif Rahman; Defri Yona; Syarifah Hikmah Julinda Sari; Nurin Hidayati (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
Banyuurip is one of the villages in Ujung Pangkah District which has potential natural resource that is mangrove forests. However, the occurrence of abrasion and conversion of mangrove land has impacted mangrove ecosystem. Rehabilitation efforts by replanting mangroves have been carried out, but they have not been effective in overcoming the current problems. The reduction of mangrove area that led the decreased of mangrove’s function can affect the livelihood of the local community, including fishermen. The installation of geosynthetic bags, which are sand-filled bags arranged on the ground, is done as an alternative solution in Banyuurip Village which functions as coastal protection and a sediment trap. The utilization of geosynthetic material is often used to help the coastal problem, the used of geosynthetic material is rarely carried out in mangrove areas. This study aims to determine the sediment characteristics, sedimentation rates, and sedimentation process based on the relationship between current velocity and sedimentation rate. The result shows that generally the type of sediment fraction in this location is silt (79,12% - 80,12%) and the rest is clay. The current installation of geosynthetic bags can result in the land extension from the trapped sediment behind the structure. In addition, the current velocity conditions and the sediment transport process also affect the sedimentation process that occurs. The average sedimentation rates around the geosynthetic bags installation area ranged from 150.72-305.01 mg.cm-2.day-1. This study may provide a basic information for further development in Banyuurip Mangrove Center and other mangrove conservation area.